الأبيض وجدلية الألوان في شعر محمد عمران - حسن, محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يدرس هذا البحث استخدام اللون في إبداع محمد عمران الشعري، حيث تبدأ الدراسة بعملية إحصائية تحصي مفردات اللون التي وردت في كامل إبداع الشاعر وصرّح بلفظها. وتركز الدراسة على مسألة هامة، وهي: علاقة اللون الأبيض ببقية الألوان الأخرى في صورتها الجدلية والتفاعلية فيما يعرف بالثنائيات الضدية، وصراع الأضداد، وما يتركه من أثر في اللوحة الشعرية ودلالاتها الإيحائية عند الشاعر، وذلك من خلال نماذج شعرية مختارة من إبداع الشاعر، غير غافلين ما يعرف برديف اللون وأثره في ذلك. This research examines the use of colour motif in the poetic creativity of M. Omran. This study starts with counting the colour vocabulary items employed plainly in the bulk of the poet's creativity. Moreover, this study focuses on an important issue, that is the relationship between the white colour and other colours in its dialectc and interactive form known as paradox. An analysis of selected poetic samples traces the impact of antonyms and their semiotic significance. The colour synonyms, needless to say, will also be referred to.